Challenge of Theileria parva (Boleni) immunised cattle with selected East African Theileria stocks - Hove, T.; Musisi, F.L.; Kanhai, G.K.; Latif, A.; Masaka, S.; Munatswa, F.C.; Pegram, R.G.; Kamwendo, S.P.; Quiroga, J.C.; Mwangondwe, R.; Dolan, T.T. (Springer, 1995)
Theileria parva (Boleni) stock from Zimbabwe was used to immunise 24 susceptible Friesian calves by infection and treatment with oxytetracycline. Twenty-eight days after immunisation the animals in groups of 6 plus 2 susceptible controls were subjected to challenge: 3 groups with heterologous stocks and one group with the immunising stock. Theileria parva (Boleni) gave good protection against homologous challenge, the T. parva (Muguga, Kenya) and buffalo-derived T. parva (Serengeti transformed, Tanzania) parasite stocks. It did not protect against the T. parva (Kasoba, Malawi) stock and 3 out of 6 immunised cattle died and athe remaining 3 had to be treated with parvaquone. In a second experiment, the 6 T. parva (Boleni) immunised animals which had received homologous challenge, together with the 2 controls which had recovered without treatment from T. parva (Boleni) infection, were challenged with the T. parva (Kasoba) stock. Four out of 6 of the immunised animals resisted the challenge with mild to moderate reactions. The other 2 animals had severe reactions and one died. The 2 control animals which recovered from T. parva (Boleni) infection resisted the T. parva (Kasoba) challenge and both had mild reactions. It is suggested that oxytetracycline used in the first experiment may have interfered with the expression of the full protective capacity against the virulent T. parva (Kasoba) stock. Further studies on the use of the T. parva (Boleni) stock without oxytetracycline treatment could identify a more broadly immunising effect and a more economical vaccination method.